Acquired phototrophy stabilises coexistence and shapes intrinsic dynamics of an intraguild predator and its prey. (1st February 2016) - Moeller, Holly V.; Peltomaa, Elina; Johnson, Matthew D.; Neubert, Michael G.
Abstract: In marine ecosystems, acquired phototrophs – organisms that obtain their photosynthetic ability by hosting endosymbionts or stealing plastids from their prey – are omnipresent. Such taxa function as intraguild predators yet depend on their prey to periodically obtain chloroplasts. We present a new theory for the effects of acquired phototrophy on community dynamics by analysing a mathematical model of this predator–prey interaction and experimentally verifying its predictions with a laboratory model system. We show that acquired phototrophy stabilises coexistence, but that the nature of this coexistence exhibits a 'paradox of enrichment': as light increases, the coexistence between the acquired phototroph and its prey transitions from a stable equilibrium to boom‐bust cycles whose amplitude increases with light availability. In contrast, heterotrophs and mixotrophic acquired phototrophs (that obtain  < 30% of their carbon from photosynthesis) do not exhibit such cycles. This prediction matches field observations, in which only strict ( > 95% of carbon from photosynthesis) acquired phototrophs form blooms.